Novel PHOX2B mutations in congenital central hypoventilation syndrome. Issue 4 (17th April 2019) - Sasaki, Ayako; Kishikawa, Yumiko; Imaji, Reisuke; Fukushima, Yu; Nakamura, Yukiko; Nishimura, Yutaka; Yamada, Megumi; Mino, Yoichi; Mitsui, Tetsuo; Hayasaka, Kiyoshi
Abstract: Background: Congenital central hypoventilation syndrome (CCHS) is caused by mutation of paird‐like homeobox 2B ( PHOX2B ). Approximately 90% of patients were found to carry polyalanine repeat expansion mutation (PARM), and the remaining 10% had non‐PARM (NPARM). In PARM, the length of the polyalanine expansion correlates with clinical disease severity. Most patients with NPARM have hypoventilation symptoms in the neonatal period and complications of Hirschsprung disease, dysregulation of autonomic nervous system, and tumors of neural crest origin. Data on the genotype–phenotype association may contribute to the clinical management of the disease. Methods: We studied the genetic background of Japanese CCHS patients according to PHOX2B sequencing. Results: Of 133 Japanese CCHS patients we identified 12 patients carrying 11 different NPARM (approx. 9% of the patients) and described the clinical manifestations in seven of them with the following novel mutations: c.941‐945del5, c.678_693dup16, c.609_616del8, c.620_633del14, c.663_711del 49, c.448C>G and c.944G>C. All patients had hypoventilation in the neonatal period and also had Hirschsprung disease, with the exception of two patients carrying c.620_633del14 and c.663_711del49 mutations. The patient carrying the c.609_616del8 mutation also had a benign mediastinal tumor. Conclusion: Most patients carrying NPARM had severe symptoms with frequent complications, as in previous reports, and should be carefully monitored for various complications, including neural crest‐derived tumor.